2020
DOI: 10.3390/cancers12123610
|View full text |Cite
|
Sign up to set email alerts
|

Second Primary Malignancy after Acute Promyelocytic Leukemia: A Population-Based Study

Abstract: Acute promyelocytic leukemia (APL), is now highly curable with treatment approaches that include all-trans retinoic acid (ATRA). The high incidence of APL in the Hispanics suggests an association with genetic variants in this population. Information on second primary malignancies (SPMs) in patients with APL is limited. The Surveillance, Epidemiology, and End Results (SEER) database was used to interrogate whether the rate of SPMs in patients with APL was associated with ethnicity and/or ATRA treatment. Between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In expansion, later information illustrate that DNMT3A mutations status has an effect on treatment choice; in one ponder, patients with DNMT3A mutations who were treated with high-dose daunorubicin compared to standard-dose treatment were appeared to have longer OS (Patel et al, 2012). However, results showed that the FLT3-ITD mutation has been identified as a marker of poor prognosis in AML, and that what most of studies agree, and the clinical outcomes of patients with FLT3-ITD-mutated AML combined with favorable cytogenetics was improved, when compared with those of patients with FLT3-ITD mono-mutated AML (Lenzi et al, 2020). Our findings showed that NPM1 mutation had a bad prognosis in AML patients and that in contrast with many studies, which they declared that OS were significantly longer for patients with NPM1 mutations.…”
Section: Discussionmentioning
confidence: 98%
“…In expansion, later information illustrate that DNMT3A mutations status has an effect on treatment choice; in one ponder, patients with DNMT3A mutations who were treated with high-dose daunorubicin compared to standard-dose treatment were appeared to have longer OS (Patel et al, 2012). However, results showed that the FLT3-ITD mutation has been identified as a marker of poor prognosis in AML, and that what most of studies agree, and the clinical outcomes of patients with FLT3-ITD-mutated AML combined with favorable cytogenetics was improved, when compared with those of patients with FLT3-ITD mono-mutated AML (Lenzi et al, 2020). Our findings showed that NPM1 mutation had a bad prognosis in AML patients and that in contrast with many studies, which they declared that OS were significantly longer for patients with NPM1 mutations.…”
Section: Discussionmentioning
confidence: 98%
“…At the neoplasm level, we also identified a number of ADEs with strong signal values. Second primary malignancy (SPM) (n = 43,) is defined as a second, distinct pathological diagnosis of the same or different origin as the first primary malignancy, and chemotherapy also increases the risk of secondary hematologic or solid malignancies (Lenzi et al, 2020;Geng et al, 2023). The mechanism of etoposide-induced second primary malignancy (SPM) can be attributed to two possible explanations.…”
Section: Neoplasms-related Adverse Reactionsmentioning
confidence: 99%
“…Previous multicentre study by the PETHEMA (Programa para el Tratamiento de Hemopatías Malignas) group characterized patients with s-MDS/AML developed after chemotherapy-based (AIDA) APL protocols. There are still few data concerning the incidence and outcomes of solid tumours after APL therapy [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%